Adjusting thermal stability in double-barrier MTJ for energy improvement in cryogenic STT-MRAMs. (August 2022) - Garzón, Esteban; De Rose, Raffaele; Crupi, Felice; Trojman, Lionel; Teman, Adam; Lanuzza, Marco
Highlights: STT-MRAMs based on double-barrier MTJ (DMTJ) operating at liquid nitrogen boiling point (77 K). Reliable, energy-efficient, and high-density STT-MRAMs operating at 77 K. DMTJ devices with relaxed retention time allow improved energy and performance at 77 K. Energy efficiency (> 35%) under write/read accesses is achieved in contrast to 6T-SRAM. Abstract: This paper investigates the impact of thermal stability relaxation in double-barrier magnetic tunnel junctions (DMTJs) for energy-efficient spin-transfer torque magnetic random access memories (STT-MRAMs) operating at the liquid nitrogen boiling point (77 K). Our study is carried out through a macrospin-based Verilog-A compact model of DMTJ, along with a 65 nm commercial process design kit (PDK) calibrated down to 77 K under silicon measurements. Comprehensive bitcell-level electrical characterization is used to estimate the energy/latency per operation and leakage power at the memory architecture-level. As a main result of our analysis, we show that energy-efficient small-to-large embedded memories can be obtained by significantly relaxing the non-volatility requirement of DMTJ devices at room temperature (i.e., by reducing the cross-section area), while maintaining the typical 10-years retention time at cryogenic temperatures. This makes DMTJ-based STT-MRAM operating at 77 K more energy-efficient than six-transistors static random-access memory (6T-SRAM) under both read and write accesses (−56% and −37% on average, respectively). Obtained results thus prove that DMTJ-based STT-MRAM with relaxed retention time is a promising alternative for the realization of reliable and energy-efficient embedded memories operating at cryogenic temperatures.